Enhancing self-care adherence in tuberculosis patients through family support: a systematic review - Falah, Miftahul; Sansuwito, Tukimin; Dioso, Regidor III; Said, Faridah Mohd.; Lismayanti, Lilis (International Journal of Public Health Science (IJPHS), 2025)
Tuberculosis (TB) is a persistent and widespread chronic disease, posing a significant global health challenge and ranking as a leading cause of mortality worldwide. Indonesia, in particular, bears the fourth-highest TB burden globally, especially within the South-East Asia (SEA) region. Alarmingly, TB incidence rates increased by 13% from 2020 to 2021. This research utilized a systematic review methodology, sourcing data from four reputable English databases: PubMed, Google Scholar, OpenAlex, and Dimensions. Both quantitative and qualitative studies published in the last five years (2019-2023) were included. A comprehensive search strategy across the specified databases yielded a total of 1,201 articles. These articles underwent meticulous screening, resulting in six articles being deemed relevant for inclusion in the review. The inclusion criteria focused on studies examining the association between family support and self-care adherence among TB patients. The systematic review identified and analyzed these six pertinent articles, highlighting the pivotal role of family support in influencing TB patients’ adherence to self-care during treatment. Enhanced family support was found to correlate positively with improved adherence levels among TB sufferers. In summary, this literature review underscores the critical importance of family support in enhancing self-care adherence for individuals undergoing tuberculosis treatment. The positive correlation between robust family support and improved adherence levels emphasizes the influential role of the family unit in the overall well-being and treatment outcomes of TB patients.